1999
DOI: 10.4098/at.arch.99-17
|View full text |Cite
|
Sign up to set email alerts
|

Winter bed-site selection by red deer Cervus elaphus xanthopygus and roe deer Capreolus capreolus bedfordi in forests of northeastern China

et al.

Abstract: Thomas, 1908 were studied in the forests of northeastern China from 1991 to 1992. Night beds used by both cervids were higher in canopy closure than day beds. Roe deer selected night bedding sites with denser canopy closure and higher percentage of coniferous trees, and day beds with better concealment cover than red deer. Roe deer selected night beds with higher canopy closure during cold mid winter period than during early and late winter period, whereas no such difference existed in day beds. Red deer show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Winter is considered to be a critical period of low availability and quality of vegetation, whereas spring is regarded as a period with gradually increasing vegetation resources to the higher points in the northern regions (Chen and Gao, 1992). Accordingly, ungulate foraging tactics will vary with food resources in order to compensate for increased energy demands in winter (Mautz, 1978;Parker and Robbins, 1984;Schmitz, 1991;Chen et al, 1999). Having grasped the mechanism of the shift in foraging tactics, especially feeding habitat selection, we can understand how animals can adapt to their surrounding environment (Jiang, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Winter is considered to be a critical period of low availability and quality of vegetation, whereas spring is regarded as a period with gradually increasing vegetation resources to the higher points in the northern regions (Chen and Gao, 1992). Accordingly, ungulate foraging tactics will vary with food resources in order to compensate for increased energy demands in winter (Mautz, 1978;Parker and Robbins, 1984;Schmitz, 1991;Chen et al, 1999). Having grasped the mechanism of the shift in foraging tactics, especially feeding habitat selection, we can understand how animals can adapt to their surrounding environment (Jiang, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Winter at higher latitudes provides an opportunity to indirectly record animal locations and behaviours such as traveling, foraging, bedding, defaecating, or urinating, by using signs left in snow (Gao et al 1995;Chen et al 1999;Jiang et al 2007). The information is particularly useful because negative energy balances during winter make this period critical for survival of many terrestrial mammals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Former research on red deer in China have shown that vegetation, slope, aspect, snow depth, other ungulate disturbances and human disturbances were important factors for feeding and bedding habitat selection of red deer (Zhang and Xiao 1990). Furthermore, selection of bed sites by red deer may reflect the energy requirements of their large bodies (Chen et al 1999). As winter can be a critical time for minimization of energy expenditure by deer, optimization of day and night bedding locations should increase survival and recruitment (Kucera 1976, Verme 1978.…”
Section: Introductionmentioning
confidence: 99%